PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN SUSTAINABILITY REPORT SEBAGAI VARIABEL MODERATING - Lating, Ade Irma Suryani (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2019)
The purpose of this study is to examine the effect of financial performance (Return On Equity, Current Ratio, Debt to Equity Ratio and Turn Asset Turn Over) on the value of the company (Price to Book Value) with Sustainability Report as a moderating variable. The sampling technique used purposive sampling method with the criteria of all companies listed in Indonesia Stock Exchange 2014-2016 with total 127 observation data. The research method used in this research is quantitative processed using statistical package for the social sciens (SPSS). The results of this research is the first Return On Equity, Debt to Equity Ratio and Turn Asset Turn Over effect on PBV, while the Current Ratio does not affect the PBV because current ratio is the ability of the company to close its short-term debt, so the current ratio is not considered a priority investors in investment decision making. Sustainability report is able to moderate the relationship between ROE, DER and TATO with PBV, while the sustainability report is unable to moderate the relationship between CR and PBV. This is because high financial performance is a must. Short-term lenders in lending only focus on financial statements, regardless of the company's social and environmental activities.